Synthesis of YBa2Cu3O7-delta - BaPbO3 composites - Lee, TG; Han, YK; Yom, SS; Cho, HS; Joo, EJ; Lee, WC; Lim, WY (KOREAN PHYSICAL SOC, 1997)
Bulk composites of YBa2Cu3O7-delta superconductors with perovskite oxide BaPbO3 added in weight percents (wt.%) of 5 similar to 30% were prepared at temperatures of 900 similar to 1000 degrees C by the conventional solid-state reaction method. Pellets sintered at temperatures between 950 degrees C and 960 degrees C showed a relatively high mass density and a large grain growth behavior. Scanning electron microscopy and electron microprobe analysis showed that slightly Yttrium-deficient rectangular-shaped YBa2Cu3O7-delta grains of up to 25 x 100 mu m(2) were embedded in the BaPbO3 matrix. The temperature dependences of the resistance and the ac-susceptibility also indicated that the inter-granular property eras significantly improved for the sample with 25 wt.% of BaPbO3 and sintered at a temperature of 960 degrees C. The composites may have improved current transport governed bg the superconductor-normal metal-superconductor type behavior of the inter-granular Josephson couplings.